2011
DOI: 10.1371/journal.ppat.1002251
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Phenotypic Profiling Defines Genes Essential for Mycobacterial Growth and Cholesterol Catabolism

Abstract: The pathways that comprise cellular metabolism are highly interconnected, and alterations in individual enzymes can have far-reaching effects. As a result, global profiling methods that measure gene expression are of limited value in predicting how the loss of an individual function will affect the cell. In this work, we employed a new method of global phenotypic profiling to directly define the genes required for the growth of Mycobacterium tuberculosis. A combination of high-density mutagenesis and deep-sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

55
1,153
5
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 959 publications
(1,218 citation statements)
references
References 46 publications
(72 reference statements)
55
1,153
5
5
Order By: Relevance
“…Since rho inactivation (Griffin et al, 2011), but not BCM treatment (Nishida et al, 1972), inhibits mycobacterial growth, the data also argue that sensitivity to the ATPase inhibitor BCM (Skordalakes et al, 2005) is not always a reliable gauge of the functional significance of Rho.…”
Section: Introductionmentioning
confidence: 94%
“…Since rho inactivation (Griffin et al, 2011), but not BCM treatment (Nishida et al, 1972), inhibits mycobacterial growth, the data also argue that sensitivity to the ATPase inhibitor BCM (Skordalakes et al, 2005) is not always a reliable gauge of the functional significance of Rho.…”
Section: Introductionmentioning
confidence: 94%
“…The reason why Crp2 appears to be essential for growth of M. smegmatis remains unknown. Analysis of the genes regulated by Crp2 (Table S3) reveals that a homologue of MSMEG_6041 in M. tuberculosis encoding fadE34 is essential for growth on cholesterol (Griffin et al, 2011). Whether MSMEG_6041 is essential for growth of M. smegmatis is not known.…”
Section: Crp1 Regulates Respiratory Energy Metabolism In M Smegmatismentioning
confidence: 99%
“…This enzyme shows a very similar homotrimeric fold and catalyses both the dCTP deamination reaction and the triphosphate hydrolysis of the resulting dUTP, directly producing dUMP from dCTP. However, the efficiency of the triphosphate hydrolysis by the bifunctional enzyme is several hundred fold less [19] than that of the monofunctional trimeric dUTPase [20].The monofunctional dUTPase (dut) is essential in Mycobacteria [21][22][23]. In contrast, earlier mutagenesis studies found that the presence of the bifunctional dCTP deaminase:dUTPase enzyme is dispensable for growth in M. tuberculosis [21,22].…”
Section: Introductionmentioning
confidence: 99%